Seasonal food habits of corsac and red foxes in Mongolia and the potential for competition - Murdoch, J; Munkhzul, T; Buyandelger, S; Reading, R; Sillero-Zubiri, C (Elsevier, 2010)
Competition often occurs between sympatric species that exploit similar ecological niches. Among canids, competition may be reduced by partitioning resources such as food, time, and habitat, but the mechanisms of coexistence remain poorly understood, particularly among fox species. We described the food habits of two foxes that live sympatrically across northern and central Asia, the corsac fox (Vulpes corsac) and red fox (v. vulpes), by analyzing scats collected during a field study in Mongolia. We analyzed 829 corsac and 995 red fox scats collected from April 2005 to August 2007 and tested the extent to which food partitioning occurred. The diets of both species consisted mainly of insects followed by rodents, but also included birds, reptiles, large mammal remains (carrion), plant material (including fruits and seeds), and garbage. Despite high overlap in the proportion of food items consumed, differences existed between species in overall diet with corsacs more frequently consuming beetles, but proportionally fewer crickets and large mammal remains than red foxes. We detected interspecific differences during the pup rearing and dispersal seasons, when prey was abundant, but not during the breeding season, when prey was scarce and diet overlap highest. Each species' diet also differed seasonally and exhibited moderate overall breadth. Corsacs consumed proportionally more beetles and rodents during pup rearing and crickets during dispersal relative to other seasons, whereas red foxes consumed proportionally more crickets during pup rearing and dispersal and more rodents and large mammals during pup rearing and breeding relative to other seasons. Our results suggest that partitioning of food resources during most of the year facilitates coexistence, and that the potential for competition is highest during winter months.